Gender and Classroom Grouping Effects on Kindergarten Children’s Self-Esteem - Asyriyah Asis; Dwi Kartika Putri; Denni Saming; Sitti Azizah Nurhady; Herman Herman (Al-Musannif, 2025)
This study aimed to examine the effects of gender and class group on the self-esteem of early childhood children. A quantitative approach with a quasi-experimental design was employed. The study was conducted at a kindergarten in Makassar, involving 80 children selected through stratified random sampling. Data were collected via structured observation using a Likert-scale instrument validated by three experts. Data analysis was performed using Two-Way ANOVA following normality and homogeneity tests. The results indicated that gender had a significant effect on children’s self-esteem, with boys exhibiting higher self-esteem than girls. In contrast, class group and the interaction between gender and class group showed no significant effects. These findings suggest that internal factors, such as gender, play a more dominant role in shaping early childhood self-esteem than structural factors, such as class grouping, highlighting the importance of gender-sensitive learning approaches to optimally support children’s self-esteem development. The study is limited by its narrow geographic scope and reliance on a single quantitative approach.